Development of Early Adolescent Emotional Maturity through Islamic Counselling (Jurnal Bimbingan dan Konseling Islam, 2022)
The study was conducted to determine whether there is an effect of Islamic guidance on emotional maturity in early adolescents. Which is where the process of providing Islamic guidance is integrated with cognitive restructuring techniques that focus on changing negative thinking patterns to positive thinking patterns so that it affects the indicators of emotional maturity, namely emotional unstability (emotional instability), emotional regression (emotional regression), social maladjustment (inability to adjust social), personality disintegration (personality disintegration), and lack of independence (less independent). This research uses quantitative research methods with experimental and descriptive approaches to get answers to predetermined problems and get wider information about cause-and-effect relationships about a phenomenon. That is how the influence of Islamic guidance in achieving emotional maturity. The research subjects were teenagers with emotional maturity problems who were students of MTsN 1 Mojokerto and SMPN 2 Bangsal. Then, the hypothesis testing of the experimental group was tested through the Wilcoxon statistical test. Based on the results of data processing, the experimental group of MTsN 1 Mojokerto obtained the Asymp value. Sig. (2-tailed) of 0.000 <0.05, it can be concluded that Ha is accepted. Then, testing the hypothesis of the experimental group at SMPN 2 Bangsal, the Asymp value was obtained. Sig. (2-tailed) of 0.006 <0.05, it can be concluded that Ha is acceptable. That is, there is an influence on the emotional maturity of adolescent students at MTsN 1 Mojokerto and SMPN 2 Bangsal after being given an intervention in the form of Islamic guidance.